Key Trends in Implementing the Fund's Transparency Policy. (Policy Papers; Policy Paper, 2015)
At the time of the 2005 Review of the Fund's Transparency Policy, the Executive Board requested regular updates on trends in implementing the transparency policy. The tables in this report provide an overview of recent developments, reflecting information on documents considered by the Board in 2014 and updating the previous annual report on Key Trends. Deeper analysis of these trends is undertaken in the context of periodic reviews of the Fund's Transparency Policy.